Religiosity and illness perception in patient with type 2 diabetes mellitus - Maslihah Maslihah; Nur Widayati; Akhmad Zainur Ridla (Universitas Muhammadiyah Semarang, 2023)
Illness perception in diabetes mellitus patients can increase uncomfortable feelings. Therefore, religiosity is needed to establish more prosperous psychological well-being. The research aimed to analyze the correlation between religiosity and illness perception in patients with type 2 diabetes mellitus. The study design was a cross-sectional approach. A total of 138 respondents were recruited using consecutive sampling. Data were collected using the Indonesian version of the Centrality Religiosity Scale 15 (CRS-15) and The Brief Illness Perception Questionnaire (B-IPQ) and analyzed using Spearman’s rho with a significant level of 0.05. The results showed that the average value of religiosity was 52.01. The median illness perception was 34.00. Based on statistical values, there was no significant correlation between religiosity and illness perception in type 2 diabetes mellitus patients (p=0,225 and r=-0,104). The absence of the correlation may be due to the assessment of the illness perception that is more directed at the patient's intellectual than the patient's emotional problem. In addition, other factors such as the availability of information and psychological distress can also affect the illness perception. This study indicates the need for further research on other factors related to the perception of disease in type 2 diabetes mellitus patients.